2009
DOI: 10.1540/jsmr.45.31
|View full text |Cite
|
Sign up to set email alerts
|

Spasmolytic effect of Psidium guajava Linn. (Myrtaceae) leaf aqueous extract on rat isolated uterine horns

Abstract: Globally, primary dysmenorrhoea is one of the most frequent gynaecological disorders in young women. It is associated with increased uterine tone, and exaggerated contractility of uterine smooth muscles. In many rural African communities, a number of medicinal plants, including Psidium guajava Linn. (family: Myrtaceae), are used traditionally for the management, control and/or treatment of primary dysmenorrhoea. The present study was, therefore, undertaken to examine the spasmolytic effect of Psidium guajava l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In this study, phytochemical analysis also shown that our plant extract contained more than 343.3728.8 mg/g of total polyphenolic content and it has been reported previously that phenolic compounds such as flavonoids and tannins have inhibitory effects on intestinal smooth muscle (Nguelefack et al, 2006;Aviello et al, 2010;Damabi et al, 2010;Kishore and Rahman, 2012;Yunita et al, 2012). Terpenoids and saponins have also been reported in other plant extracts to exhibit antispasmodic and vasodilatatory effects on smooth muscle preparations (Ghayur et al, 2005;Chiwororo and Ojewole., 2009;Dubravka et al, 2010). The presence of these bioactive compounds in the aqueous extract of P. mannii might explain at least in part the observed effects on rat duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, phytochemical analysis also shown that our plant extract contained more than 343.3728.8 mg/g of total polyphenolic content and it has been reported previously that phenolic compounds such as flavonoids and tannins have inhibitory effects on intestinal smooth muscle (Nguelefack et al, 2006;Aviello et al, 2010;Damabi et al, 2010;Kishore and Rahman, 2012;Yunita et al, 2012). Terpenoids and saponins have also been reported in other plant extracts to exhibit antispasmodic and vasodilatatory effects on smooth muscle preparations (Ghayur et al, 2005;Chiwororo and Ojewole., 2009;Dubravka et al, 2010). The presence of these bioactive compounds in the aqueous extract of P. mannii might explain at least in part the observed effects on rat duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that PMAE partially but significantly inhibited in a concentration-dependent manner the contractile response elicited by carbachol or histamine on rat duodenum. Smooth muscles contraction, in response to histamine or carbachol is initiated by the increase of the cytoplasmic-free Ca 2 þ concentration.These agonists directly activate their specific receptors on the membrane of gastrointestinal smooth muscle cells (Rodriguez et al, 2006;Gilani et al, 2008), which results in activation of several intracellular pathways and production of second messengers (phospholipase C, inositol triphosphate, diacylglycerol, protein kinase C) which in turn stimulate the release of internal Ca 2 þ from sarcoplasmic reticulum stores and the Ca 2 þ influx through voltage-gated Ca 2 þ channels (Chiwororo et al, 2009;Desire et al, 2010;Dubravka et al, 2010;Hu et al, 2010). Therefore, the inhibitory effects of PMAE on carbachol-or histamine-induced contractions could be produced as a result of a blockage of muscarinic or histaminic receptors on the cell membrane, or a calcium channel blocking activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All drugs were dissolved and/or diluted in distilled water on each day of our experiments [28] . Drugs concentrations quoted in the text refer to final organ-bath concentration.…”
Section: E Chemicals Usedmentioning
confidence: 99%